Effect of Metformin on Adenosine Deaminase Activity in Polycystic Ovarian Syndrome patients - Faisal Gh. Al-Rubaye; Taha Shawi Morad; Maysoon A. Ahmed (Journal of Madenat Alelem University College, 2014)
This study was done to assess the role of adenosine deaminase (ADA) in women with polycystic ovarian syndrome (PCOS) on metformin therapy. The present study is a cross-sectional study (2011/2012) at Al-yarmouk teaching hospital. A total of 80 patients with PCOS were involved in this study, they were classified as newly diagnosed women with PCOS G1: (n=40);women with PCOS on metformin therapy 500 mg (bid) for 90 days G2: (n=40). A matching group of forty apparently healthy women who were included as controls(n=40). Serum ADA was measured in all women and it was significantly reduced in women with PCOS receiving metformin therapy when compared with newly diagnosed patients with PC (p < 0.001) also a significant reduction was found when controls compared with the newly diagnosed women (p < 0.001); however, the reduction was insignificant when controls compared with treated group (p < 0.05). In conclusion,the results of this study suggest that the metformin currently used by PCOS patients has indirect effect on ADA activity through improving insulin sensitivity.